Two new ‘legumoviruses’ (genus Begomovirus) naturally infecting soybean in Nigeria - Alabi, O.J.; Kumar, P. Lava; Mgbechi-Ezeri, J.U.; Naidu, R.A. (Springer, 2010)
Two new ‘legumoviruses’ (genus Begomovirus; family Geminiviridae) naturally infecting soybean (Glycine max L. Merr.) in Nigeria were molecularly characterized. Based on characteristic symptoms in soybean, the two viruses are provisionally designated as Soybean mild mottle virus (SbMMV) and Soybean chlorotic blotch virus (SbCBV). SbCBV has a bipartite genome, whereas SbMMV has only a DNA A component. The DNA A component of SbMMV is 2,768 nucleotides (nt) long and the DNA A and DNA B components of SbCBV are 2,708 and 2,647 nt long, respectively. In pairwise comparisons, the DNA A component of SbMMV and SbCBV showed 62% nt sequence identity, indicating that these two viruses are distinct. Whereas the DNA A of SbMMV contains two virion- and four complementary-sense open reading frames, that of SbCBV lacks the virus-sense AV2, a signature gene present in ‘Old World’ begomoviruses. A pairwise comparison with the corresponding nucleotide sequence of other begomoviruses in the databases indicated that SbCBV had a maximum of 74% identity with cowpea golden mosaic virus and SbMMV had a maximum of 65% identity with mungbean yellow mosaic India virus and kudzu mosaic virus. Phylogenetic analysis of the DNA A component of SbCBV and SbMMV together with those of other begomoviruses available in the databases showed clustering of the two viruses within the ‘legumovirus’ clade of the begomovirus phylogenetic tree. In addition, the DNA A and B components of SbCBV from Centrosema pubescens Benth were found to be identical to those from soybean, indicating that leguminous wild species are a potential alternative host for the virus. Since soybean is an introduced crop, the identification of two distinct begomoviruses naturally infecting soybean in Nigeria suggests the occurrence of ‘legumoviruses’ in plant species indigenous to Africa and underscores their potential threat to sustainable cultivation of soybean on the African continent.